Analisis Komparatif Risiko dan Return Pada Saham dan Obligasi di Bursa Efek Indonesia: Implikasi Bagi Investor - Syamsudin Syamsudin; Muammar Khaddafi (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study analyzes the characteristics, risk, and return of stocks and bonds in Indonesia. The data used is historical data on stock and bond prices traded on the IDX during a 10-year period, from 2014 to 2024. The analysis methods used are descriptive analysis, t-test, ANOVA, and multiple linear regression. The results of the study show that stocks offer the potential for higher returns than bonds, but also with higher risk. Bonds offer better income stability and lower risk than stocks. The investment decision between stocks and bonds depends on the individual's risk profile and investment goals. Diversification remains an important investment strategy, regardless of risk profile.